Nudging Finnish Adults into Replacing Red Meat with Plant-Based Protein via Presenting Foods as Dish of the Day and Altering the Dish Sequence - Nykänen Esa-Pekka; Hoppu Ulla; Löyttyniemi Eliisa; Sandell Mari (MDPI, 2022)
This study investigated whether Finnish working-aged omnivores (n = 163) could be nudged into replacing red meat with a fava-bean-based protein source via "Dish of the Day" (DoD) and main dish sequence alteration (SA) strategies in a controlled real-world Finnish self-service buffet restaurant with smart scales (Flavoria (R) Multidisciplinary Research Platform). A further aim was to study whether the effectiveness of the strategies differed by gender, age, and body mass index. The participants were assigned one of four experimental treatments: standard menu (T1), DoD (T2), standard menu + SA (T3), or DoD + SA (T4). The participants could choose any amount or combination of salad components and casseroles with minced meat or fava bean protein. Being subjected to a DoD menu and/or SA had no effect on main dish choice or the share of the meat-based dish in the meal weight. Men were more likely to choose a meat-based main dish and had a higher share of the meat dish in the meal weight compared to women, but no differences were observed between those aged 18-29,30-44, or 45-65 years or those who were normal weight, overweight, or obese. Future studies should have a larger sample size and investigate food choice motives such as price or environmental awareness.